ANALISIS TINGKAT KETAHANAN PANGAN RUMAH TANGGA PETANI JAGUNG DI DESA BANDAR JAYA KECAMATAN LENGKITI KABUPATEN OGAN KOMERING ULU (JASEP, 2018)
Analysis of Household Food Security Corn Growers In Bandar Desa Jaya subdistrict Lengkiti Konering Ulu Ogan. Research this aim for calculate as where the level of food security corn farmer in the village of Bandar Jaya subdistrict Lengkiti OKU District. Method The research in is Method Surveys. The method used data in research in tian this is observation and Interview with questionnaire as tool data collection. The data used is the primary data is data obtained directlyfrom field with use questionnaire as tool collecting data an secondary data namely data obtained from agencies - related agencies in research this. Based on the research that has been done to the corn farmers in the village of Bandar Jaya subdistrict Lengkiti Ulu Ogan Ogan, it can be concluded the level of household food security corn growers are at the level of pwishful resistant because pengeluaranya share of <60%.